Experiences of gardening during the early stages of the COVID-19 pandemic. (July 2022) - Kingsley, Jonathan; Diekmann, Lucy; Egerer, Monika H.; Lin, Brenda B.; Ossola, Alessandro; Marsh, Pauline
Abstract: Gardening has the potential to improve health and wellbeing, especially during crises. Using an international survey of gardeners (n = 3743), this study aimed to understand everyday gardening experiences, perspectives and attitudes during early stages of the COVID-19 pandemic in 2020. Our qualitative reflexive thematic and sentiment analyses show that during the first months of the COVID-19 pandemic, gardening seemed to create a safe and positive space where people could socially connect, learn and be creative. Participants had more time to garden during the pandemic, which led to enhanced connections with family members and neighbours, and the ability to spend time in a safe outdoor environment. More time gardening allowed for innovative and new gardening practices that provided enjoyment for many participants. However, our research also highlighted barriers to gardening (e.g. lack of access to garden spaces and materials). Our results illustrate the multiple benefits of gardening apparent during COVID-19 through a lens of the social-ecological model of health. Highlights: Gardening has multiple health benefits that have been amplified during COVID-19. During the pandemic people had more time to learn and be creative in gardens. Gardens for most participants were a safe haven for social connections.